Wealth Inequality in the Netherlands, c. 1950-2015. The Paradox of a Northern European Welfare State - Van Bavel, Bas; Frankema, Ewout (TSEG - The Low Countries Journal of Social and Economic History, 2017)
This paper reviews the available evidence on post-war trends in Dutch private wealth inequality using a range of scattered sources. Wealth tax records suggest a substantial decline in inequality to the 1970s and, more tentatively, a gradual rise thereafter. In the post-1990 years, Gini-coefficients of private wealth inequality range from 0.8 to 0.9, which is at the high end of the international comparison. Such high levels of private wealth inequality contrast with relatively low levels of net income inequality; a paradox that the Netherlands share with other Northern European welfare states. We hypothesise that publicly funded life-time income security limits the wealth-formation by ordinary Dutch households, while the redistributive taxes required to finance this system are targeting income rather than wealth.